Perinatal imaging findings and molecular genetic analysis of thanatophoric dysplasia type 1 in a fetus with a c.2419T>G (p.Ter807Gly) (X807G) mutation in FGFR3 - Shin-Wen Chen; Chih-Ping Chen; Liang-Kai Wang; Schu-Rern Chern; Pei-Chen Wu; Yen-Ni Chen; Chen-Ju Lin; Wen-Ling Chen; Wayseen Wang (Taiwanese Journal of Obstetrics & Gynecology, 2017)
Objective: We present perinatal imaging findings and molecular genetic analysis of thanatophoric dysplasia type I (TD1) in a fetus. Case Report: A 28-year-old woman was referred for genetic counseling at 22 weeks of gestation because of abnormal prenatal ultrasound findings. Level II ultrasound examination revealed a narrow chest, shortened and curved long limbs, protrusion of the abdomen, and macrocephaly. A tentative diagnosis of TD1 was made. After genetic counseling, the pregnancy was terminated and a malformed fetus was delivered. Postnatal radiography findings were consistent with the diagnosis of TD1, with additional findings of short ribs, platyspondyly, and horizontal acetabular roofs. Molecular genetic analysis using umbilical cord tissue revealed a heterozygous mutation of c.2419T>G (p.Ter807Gly) (X807G) in the fibroblast growth factor receptor 3 gene (FGFR3). Conclusion: A second-trimester fetus with a heterozygous c.2419T>G mutation in FGFR3 may present characteristic ultrasound and X-ray findings of TD1.